2023
DOI: 10.1007/jhep01(2023)030
|View full text |Cite
|
Sign up to set email alerts
|

On the Nekrasov partition function of gauged Argyres-Douglas theories

Abstract: We study SU(2) gauge theories coupled to (A1, DN) theories with or without a fundamental hypermultiplet. For even N, a formula for the contribution of (A1, DN) to the Nekrasov partition function was recently obtained by us with Y. Sugawara and T. Uetoko. In this paper, we generalize it to the case of odd N in the classical limit, under the condition that the relevant couplings and vacuum expectation values of Coulomb branch operators of (A1, DN) are all turned off. We apply our formula to the (A2, A5) theory t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…We have explicitly discussed this in the example of the (A 2 , D 4 ) theory. It was observed in [117,118] that the Schur indices for this class of theories can be written in terms of that of N = 4 SYM theory upon rescaling of fugacities (see also the comment in [133]). It would be nice to investigate in future work whether these connections between the N = 2 SCFTs with a = c and the N = 4 SYM are actually related or not.…”
Section: Discussionmentioning
confidence: 99%
“…We have explicitly discussed this in the example of the (A 2 , D 4 ) theory. It was observed in [117,118] that the Schur indices for this class of theories can be written in terms of that of N = 4 SYM theory upon rescaling of fugacities (see also the comment in [133]). It would be nice to investigate in future work whether these connections between the N = 2 SCFTs with a = c and the N = 4 SYM are actually related or not.…”
Section: Discussionmentioning
confidence: 99%
“…Then it was shown that the corresponding gauge counterparts in case of r = 2 and r = 3 are just the AD theories denoted by H 1 and H 2 respectively. Such relationships were subject of further detailed investigation in [14][15][16][17][18][19][20][21][22]. In a parallel development it was shown in [23] that H 1 and H 2 partition functions are closely related to third and forth PainlevĆ© Ļ„ -functions provided ā„¦-background parameters are subject to condition Ļµ 1 = āˆ’Ļµ 2 .…”
Section: Introductionmentioning
confidence: 98%